2020
DOI: 10.1037/xge0000646
|View full text |Cite
|
Sign up to set email alerts
|

Gesture–speech physics: The biomechanical basis for the emergence of gesture–speech synchrony.

Abstract: Note that parts of the current manuscript may overlap verbatim with the pre-registration. Open data & Pre-registration: This study has been pre-registered on the Open Science Framework (OSF: https://osf.io/5aydk/) and the raw anonymized quantitative data, and analyses scripts supporting this confirmatory study are also available on the OSF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(85 citation statements)
references
References 47 publications
9
75
0
1
Order By: Relevance
“…For example, it has been found, in the pronunciation of the nonsense word "baba," when stress is put on the first (baba) or last syllable (baba), the pointing gesture's maximum extension is coordinated to align more closely with the stressed syllable (Rochet-Capellan, Laboissiere, Galvan, & Schwartz, 2008; see also Esteve-Gibert & Prieto, 2013;Krivokapić, Tiede, & Tyrone, 2017;Rusiewicz, Shaiman, Iverson, & Szuminsky, 2014). On the biomechanical level, it has further been found that gesture's moments of peak physical impetus (lasting~50 ms) entrain fundamental frequency and the amplitude envelope during phonation (Pouw, Harrison, & Dixon, 2019). Wim Pouw and James P. Trujillo contributed equally to the present manuscript and share first authorship Thus, the gesture-speech relationship is defined over many levels and timescales (for overviews, see Kendon, 2004;Wagner et al, 2014).…”
mentioning
confidence: 99%
“…For example, it has been found, in the pronunciation of the nonsense word "baba," when stress is put on the first (baba) or last syllable (baba), the pointing gesture's maximum extension is coordinated to align more closely with the stressed syllable (Rochet-Capellan, Laboissiere, Galvan, & Schwartz, 2008; see also Esteve-Gibert & Prieto, 2013;Krivokapić, Tiede, & Tyrone, 2017;Rusiewicz, Shaiman, Iverson, & Szuminsky, 2014). On the biomechanical level, it has further been found that gesture's moments of peak physical impetus (lasting~50 ms) entrain fundamental frequency and the amplitude envelope during phonation (Pouw, Harrison, & Dixon, 2019). Wim Pouw and James P. Trujillo contributed equally to the present manuscript and share first authorship Thus, the gesture-speech relationship is defined over many levels and timescales (for overviews, see Kendon, 2004;Wagner et al, 2014).…”
mentioning
confidence: 99%
“…Rusiewicz et al, 2013Rusiewicz et al, , 2014. Pouw and Dixon (2019) found that a Delayed Auditory Feedback actually increases the temporal alignment between gestures and speech. Lastly, Bergmann et al, (2011) found that gestures and speech were more temporally aligned when their semantic content was more similar.…”
Section: Temporal Alignmentmentioning
confidence: 99%
“…Moreover, this tight coupling has been conceptualized as gesture-speech synchronization (e.g. Iverson & Thelen, 1999;Pouw & Dixon, 2019;Treffner & Peter, 2002). Gestures and speech synchronize in time, semantic content, emphasis, and emotional valence (for a comprehensive review, see Wagner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, a possible candidate gesture-speech invariant was identified (Pouw, Harrison, et al, 2019). Namely, when steady-state vocalizing a vowel /a:/ (as in cinema), highimpetus whole-arm upper limb movements imparted positive peaks in the amplitude envelope and F0 of phonation acoustics.…”
mentioning
confidence: 99%
“…The dynamics of the hypothesized gesture-induced forces on the lower vocal tract are still unknown. We hypothesized that physical impulses produced by acceleration and decelerations in gesture, are not kept locally contained at the effector muscles (Pouw, Harrison, et al, 2019).…”
mentioning
confidence: 99%